2010
DOI: 10.3109/10715762.2010.524643
|View full text |Cite
|
Sign up to set email alerts
|

Succination of proteins in diabetes

Abstract: Cysteine is arguably the most reactive amino acid in protein. A wide range of cysteine derivatives is formed in vivo, resulting from oxidation, nitrosation, alkylation and acylation reactions. This review describes succination of proteins, an irreversible chemical modification of cysteine by the Krebs cycle intermediate, fumarate, yielding S-(2-succinyl)cysteine (2SC). Intracellular fumarate concentration and succination of proteins are increased by hyperpolarization of the inner mitochondrial membrane and dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 47 publications
1
45
0
Order By: Relevance
“…Succination is a distinct process from succinylation, which typically occurs on lysine residues and is considered to be mediated by succinyl coenzyme A, producing a thioester derivative protein product (79). Recently, increases in protein succinylation have also been shown to occur under conditions where succinate levels are elevated and the activity of the desuccinylase SIRT5 is suppressed.…”
Section: Figurementioning
confidence: 99%
“…Succination is a distinct process from succinylation, which typically occurs on lysine residues and is considered to be mediated by succinyl coenzyme A, producing a thioester derivative protein product (79). Recently, increases in protein succinylation have also been shown to occur under conditions where succinate levels are elevated and the activity of the desuccinylase SIRT5 is suppressed.…”
Section: Figurementioning
confidence: 99%
“…Our findings also indicate that adiponectin suppresses ER stress through the XBP-1, ATF-4 and ACC pathway in the liver of the nSREBP1c/adiponectin transgenic mice. Adiponectin is known to suppress ER stress in obesity and diabetes (16,17). Recent studies have linked ER stress to obesity, insulin action and type 2 diabetes (18,19), and the activation of the UPR is governed by three ER transmembrane proteins: inositol-requiring kinase-1 (IRE1), protein kinase-like ER kinase (PERK) and activating transcription factor-6 (ATF6).…”
Section: Discussionmentioning
confidence: 99%
“…The positive association between mitochondrial membrane potential oscillations and fasting plasma glucose within the range from normal to dysglycemic conditions suggested that hyperglycaemic challenge implied increased glucose metabolisation, enhanced oxidant formation and hyperpolarisation of the mitochondrial membrane. It is noteworthy that succination of proteins, which is an irreversible chemical modification of cysteine by the Krebs cycle intermediate fumarate, is increased by hyperpolarisation of the inner mitochondrial membrane and develops in concert with mitochondrial and oxidative stress in diabetes (Frizzell et al, 2011).…”
Section: Biochemical Phenotype and Redox Balance In Type 1 Diabetes Rmentioning
confidence: 99%